2012
DOI: 10.1371/journal.pone.0041011
|View full text |Cite
|
Sign up to set email alerts
|

Tenofovir Use and Renal Insufficiency among Pregnant and General Adult Population of HIV-infected, ART-Naïve Individuals in Lilongwe, Malawi

Abstract: BackgroundThe Malawian government recently changed its prevention of mother-to-child transmission (PMTCT) regimen and plans to change its first-line antiretroviral therapy (ART) regimen to Tenofovir(TDF)/Lamivudine/Efavirenz as a fixed-dose combination tablet. Implementation could be challenging if baseline creatinine clearance (CrCl) screening were required to assess renal function prior to TDF therapy. Our goal is to determine predictors of CrCl<50 ml/min among HIV-infected, ART-naïve individuals.Methodology… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
10
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 24 publications
(23 reference statements)
2
10
0
Order By: Relevance
“…This analysis documents risk factors for prevalent renal dysfunction in patients initiating ART that are similar to those identified by previous studies from sub-Saharan Africa including low haemoglobin or anaemia (Mulenga et al 2008;Johnson et al 2012), older age and lower CD4 cell counts before ART initiation (Franey et al 2009;Bygrave et al 2011). Although we found that women had higher relative odds of renal impairment at baseline, women also showed greater improvement in renal function over time.…”
Section: Discussionsupporting
confidence: 68%
See 1 more Smart Citation
“…This analysis documents risk factors for prevalent renal dysfunction in patients initiating ART that are similar to those identified by previous studies from sub-Saharan Africa including low haemoglobin or anaemia (Mulenga et al 2008;Johnson et al 2012), older age and lower CD4 cell counts before ART initiation (Franey et al 2009;Bygrave et al 2011). Although we found that women had higher relative odds of renal impairment at baseline, women also showed greater improvement in renal function over time.…”
Section: Discussionsupporting
confidence: 68%
“…; Johnson et al . ), older age and lower CD4 cell counts before ART initiation (Franey et al . ; Bygrave et al .…”
Section: Discussionmentioning
confidence: 99%
“…; Johnson et al . ). This phenomenon is explained in part by the haemodilution of pregnancy, resulting in lower absolute CD4 cell counts per microlitre in pregnant women relative to non‐pregnant adults at a similar stage of clinical disease progression (Gelson et al .…”
Section: Discussionmentioning
confidence: 97%
“…In turn, these data suggest that the risks of acute nephrotoxicity associated with immediate tenofovir initiation without prior screening of serum creatinine results appears minimal, in keeping with other data from primary care populations in Africa (Johnson et al . ). Other putative risks related to rapid ART initiation in pregnant women, including limited time for patient education and counselling prior to ART initiation, have not been demonstrated to adversely affect patient outcomes (Myer et al .…”
Section: Discussionmentioning
confidence: 97%
“…Tenofovir inclusion in highly active antiretroviral therapy regimens in the treatment of Human Immunodeficiency Virus (HIV)/Acquired Immune Deficiency Syndrome (AIDS) has clinically shown to have an excellent efficacy and safety outcomes when compared with HAART regimens containing other first-line antiretroviral drugs, such as abacavir (ABC), stavudine (d4T) and zidovudine (AZT) [1,2]. Although TDF use has been associated with acceptable safety, several studies have reported a rare manifestation of renal disease in HAART regimens that include TDF [3][4][5][6][7][8].…”
Section: Social Valuementioning
confidence: 99%